2014
DOI: 10.1002/hbm.22490
|View full text |Cite
|
Sign up to set email alerts
|

Comparing within‐subject classification and regularization methods in fMRI for large and small sample sizes

Abstract: In recent years, a variety of multivariate classifier models have been applied to fMRI, with different modeling assumptions. When classifying high-dimensional fMRI data, we must also regularize to improve model stability, and the interactions between classifier and regularization techniques are still being investigated. Classifiers are usually compared on large, multisubject fMRI datasets. However, it is unclear how classifier/regularizer models perform for within-subject analyses, as a function of signal stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
(89 reference statements)
1
18
0
Order By: Relevance
“…On the other hand, improvements beyond ~100 subjects were very small and appeared to approach a limiting value. This closely resembles findings on multivariate modelling of fMRI data (Churchill et al, 2014). The authors also observed that increases in sample size led to a plateau in regards to prediction accuracy already with small samples, while reproducibility of model parameters improved if already large samples were increased.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, improvements beyond ~100 subjects were very small and appeared to approach a limiting value. This closely resembles findings on multivariate modelling of fMRI data (Churchill et al, 2014). The authors also observed that increases in sample size led to a plateau in regards to prediction accuracy already with small samples, while reproducibility of model parameters improved if already large samples were increased.…”
Section: Discussionsupporting
confidence: 84%
“…One option is to average the predictions of a set of suitable models [44, chap. 35], [8,23,29] -see [18, chap. 8] for a description outside of neuroimaging.…”
Section: Hyper-parameter Selectionmentioning
confidence: 99%
“…Although the biological interpretations of these algorithms are not mutually exclusive to ICA, the success of a specific dictionary learning method may prioritize theories of encoding. Moreover, given the finding that the choice of regularizer may be more important than the choice of classifier ([19]), judicious selection a priori of a regularization method may allow us to better understand the network dynamics of cognitive processes.…”
Section: Introductionmentioning
confidence: 99%